Impact of tides and sea-level on deep-sea Arctic methane emissions - Sultan, Nabil; Plaza-Faverola, Andreia; Vadakkepuliyambatta, Sunil; Buenz, Stefan; Knies, Jochen (Nature Communications, 2020)
Sub-sea Arctic methane and gas hydrate reservoirs are expected to be severely impacted by ocean temperature increase and sea-level rise. Our understanding of the gas emission phenomenon in the Arctic is however partial, especially in deep environments where the access is difficult and hydro-acoustic surveys are sporadic. Here, we report on the first continuous pore-pressure and temperature measurements over 4 days in shallow sediments along the west-Svalbard margin. Our data from sites where gas emissions have not been previously identified in hydro-acoustic profiles show that tides significantly affect the intensity and periodicity of gas emissions. These observations imply that the quantification of present-day gas emissions in the Arctic may be underestimated. High tides, however, seem to influence gas emissions by reducing their height and volume. Hence, the question remains as to whether sea-level rise may partially counterbalance the potential threat of submarine gas emissions caused by a warmer Arctic Ocean.